Development of a UPLC-MS/MS method for the determination of sulfatinib and its no interaction with myricetin in rats - Chen, Dongxin; Chen, Jie; Xia, Hailun; Chen, Xiaohai; Hu, Jinyu; Wu, Guangliang; Xu, Xuegu (Frontiers in Pharmacology, 2024)
Sulfatinib is a novel oral tyrosine kinase inhibitor (TKI) with selective inhibition of fibroblast growth factor (FGFR), colony-stimulating factor 1 receptor (CSF-1R) and vascular endothelial growth factor receptor (VEGFR) 1, 2 and 3. It has been approvedfor the therapy of neuroendocrine tumors arising in the non-pancreatic (December 2020) and pancreatic (June 2021) glands. Until now, there has no research on the determination of sulfatinib in biological medium by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method. The current study validated a sensitive and reliable quantitative detection of sulfatinib in plasma using UPLC-MS/MS for the first time, and investigated the interaction with myricetin in rats. Acetonitrile was used to precipitate the plasma protein, and lenvatinib was employed as the internal standard (IS). The method demonstrated that sulfatinib presented high linearity over the concentration of 1-2000 ng/mL with the lower limit of quantification (LLOQ) of 1 ng/mL. It was validated methodologically that the precision, matrix effect, stability, accuracy and extraction recovery were all within the allowable values. Moreover, male Sprague-Dawley (SD) rats were assigned randomly to assess the interaction between sulfatinib (30 mg/kg) and myricetin (50 mg/kg). Nevertheless, no significant differences of the main pharmacokinetic parameters were revealed. This may be due to insufficient doses of myricetin, or failure of myricetin to act in a timely manner in vivo. The findings contributed to a better understanding of the metabolism and drug-drug interaction of sulfatinib, but the presence or absence of interactions needs to be confirmed by further studies.